Nephrotoxic Effects of Odogwu Bitters Herbal Drink in Adult Male Wistar Rats - Onyejike, Darlingthon; Okafor, Emeka; Ezeugo, Chioma; Nwamaradi, Albert; Onyejike, Ifeoma; Okwuonu, Ifeoma; Okeke, Somadina; Obiesie, Ifechukwu (Nigerian Journal of Basic and Clinical Sciences, 2025)
Context:Herbal alcoholic drinks, like other alcoholic beverages, can be intoxicating and potentially harmful to the kidneys and other vital organs when consumed excessively. This study investigated the nephrotoxic effects of graded doses of Odogwu Bitters herbal alcoholic drink in adult male Wistar rats. Materials and Methods:Sixteen adult male Wistar rats, weighing 195–230 g, were divided into four groups (A–D) of four rats each. Group A served as the control and received only feed and water. Experimental groups received daily doses of Odogwu Bitters: Group B (0.45 mL), Group C (0.75 mL), and Group D (1.05 mL). The study duration was five weeks. Kidney function tests (creatinine, urea, and uric acid) were performed, and renal histology was examined for structural changes. Results:Histological analysis showed no pathological changes in Group B, while Groups C and D exhibited mild mesangial hypercellularity. Kidney function tests revealed no statistically significant differences between the control and experimental groups for creatinine, urea, and uric acid levels. Conclusion:Moderate and high doses of Odogwu Bitters consumed over five weeks caused mild renal changes, whereas low doses did not adversely affect kidney function or histology. These findings suggest that mild consumption may be relatively safe for renal health, while higher doses may exert mild nephrotoxic effects.